Analysis of Defect Improvement at LG Compressor Assembly Plant - Ghosh, Dwipayan (My University, 2022)
The objective of this practical training is to learn something about industries practically and to be familiar with a working style of a technical worker to adjust simply according to industrial environment. This report deals with the equipment their relation and their general operating principle. In this project work the layout of LG Compressor plant has been studied, right from machine shop to production line to final dispatch line. Compressors produced during this plant are hermetically sealed compressors which are fitted in refrigeration units. In addition to those compressors usage in refrigerators these are also dispatched to other industries as well as exported to other countries. Different models of compressors are manufactured depending upon the dimensions and capacity of refrigeration unit. Detailed study of various assembly line defects starting from Drop line to final line and LQC section has been done. Lock pin defect reloading rate has been reduced from 5% to 1% when the machines were set with in the specification limit, higher piston jam defect reloading rate has been reduced after the piston and c-block size chamfer has been reduced and cover silencer final bolting machine set up to specification limit. Also, for the air gap defect a comparison has been made between CMA062 and CMA069 model for checking rotor runout and was found that in some rotor’s runout is above the specification limit coming from the vendor.
Keywords: Hermetically Sealed compressor; LQC section; line defects